Possibilities of Organizing Independent Education for Future Chemistry Teachers - Formanova Shoira Bobonazarovna (Researchparks Publishing, 2023)
In this article of students independent the work assignments competence of formation theoretical conditions clarification about take went research results to the analysis circle thought and considerations are given.